Benz Limit Optimal Design for Double Fed Induction Generator and Kundru’s Multimachine integration - Abel E. Airobman; Sabo Aliyu2; Engr. Musa (Universitas Negeri Surabaya or The State University of Surabaya, 2026)
The study explores the integration of an optimal Benz limit Doubly Fed Induction Generator (DFIG) with IEEE Kundur's test multi-machine power system, emphasizing the use of meta-heuristic algorithms and controllers.his work is scoped at the DFIG power coefficient, output voltage, and phase angle oscillations during integration. The controllers’ performances were compared with three techniques: the hippopotamus (HO), Sine cosine (SC), and Morth flame (MFO) algorithms to verify the competence of the proposed method in achieving better system stability. To improve the proposed Hybrid Multi-source integration of DFIG, Hydrogen Fuel Cell (HFC) to augment (Wind, Solar cell, Battery energy storage system), the proposed work presents the mathematical formulation of DAE, the designed models, and the implementation of wind aerodynamic/mechanical coupling shaft. ODE as solver in MATLAB 2021a Simulink environment as presented. The results presented an optimal Benz limit for the blade tip speed ratio = 8.1, blade pitch angle =0, rotor power coefficient = =0.48, and turbine output power =5 MW described by equation 7. A symmetrical fault was set up on bus 2 at t = 1 second; the governor load reference increased by 1%, the system loading by 1%; and a nonlinear time-domain simulation was carried out on the integrated network to assess controllers’ robustness Likewise, the result validates the usefulness of the proposed SC, HO, and MFO tuned Tilt, PID for DFIG output voltage and phase angle control that outperforms the traditional MFO tuning techniques in terms of resilience, efficiency, and convergence.